Evaluation of internal coupling and coordination degree and diagnosis of obstacle factors for high-quality regional economic development: Evidence from Chongqing's " One District, Two Groups". - Sifang Che; Xi Zhang; Weijia Shu (PLoS ONE)
The study builds a high-quality development index system encompassing dimensions of economic vitality, coordinated development, green development, and digital development. Utilizing the entropy weight TOPSIS method, the coupling coordination model, and the barrier factor model, this research examines the high-quality economic development level, internal coupling coordination, and obstacle factors in Chongqing's "one district and two groups" from 2017 to 2021. The findings are as follows: (1)The high-quality economic development level of the "one district and two groups" has been increasing year by year. This growth is driven by the joint progress across all dimensions, though regional disparities exist in the development levels of different dimensions. The order of high-quality economic development from highest to lowest is: the main city metropolitan area, southeast Chongqing, and northeast Chongqing. (2)The development level of internal coupling coordination for high-quality economic development within the "one district and two groups" has also been rising annually. However, the overall level of coupling coordination development remains low, although regional coupling coordinated development is gradually forming. There was no evidence of σ convergence in the coupling coordination of high-quality economic development within the "one district and two groups." The main city metropolitan area shows stability with an expansion trend, while the "two groups" exhibit divergence. (3)Overall, Chongqing's barrier index order was "economic vitality > coordinated development > green development > digital development." There were differences in obstacle factors between "one district" and "two groups"; the "two groups" align with the overall performance, while the main metropolitan area performs as "green development > economic vitality > coordinated development > digital development." The research conclusions provide a theoretical basis and decision-making reference for improving coordinated development within the region. (4)The main obstacles to high-quality economic development in Chongqing and the "one district and two groups" are centered on the dimensions of economic vitality and coordinated development, while also reflecting green development considerations.